. - Sosa, Roxana (Nomadías, 2010)
This paper is a brief analysis of creative thinking considered from the artistic perspective. For this approach the role of the creative subject as fundamental to art that gets made effective, noting how this individual has been shaped through history thanks to the denial of other subjects, and among women artists. In this sense the artistic creation has been traditionally held by men, and they have moved to their works that was dominant in society, being thus the ratio of women to art has been conditioned by a sexist.